Faktor-faktor yang Mempengaruhi Kinerja Tenaga Penjualan: Keinovatifan dan Orientasi Pelanggan - Maria Augustine Graciafernandy; Suhaji Suhaji; Tantri Widiastuti (STIE Widya Manggala, 2022)
Salesforce is the spearhead of marketing in a business. Salesforce also plays role as a representative of the company’s performance and image. This study based on the decreasing of salesforce performance on life insurance industry. This study aimed to analyse the effect of salesforces innovativeness and customer orientation on salesforce performance. The main data in this study was collected from the questionnaires answered by the sales forces of life insurance industry in Semarang. The response given by 52 respondents from joint venture insurance companies who hold an AAJI license then be analyzed by using SPSS. The result empirically showed that customer orientation had a positive effect on sales force performance. On the other hand the variable sales force innovativeness did not give the same effect as customer orientation. Simultaneuosly all independen variables had a significant effect on sales force performance.